Sensitivity of colletotrichum gloeosporioides to sodium bicarbonate on the development of anthracnose in papaya (Carica papaya L. cv. Frangi) - Hasan, Maroof F.; Mahmud, Mohamed Muda Mohamed; Kadir, Jugah; Ding, Phebe; Sarker, Md. Zaidul Islam (Southern Cross Journals, 2012)
Using of non-chemical control methods to reduce postharvest decay is becoming increasingly important in both economic and environmental view point. Sodium bicarbonate (SBC) is a common food additive recognized as safe substance in food industry. This study had been carried out to look at the ability in both in vitro and in vivo conditions of sodium bicarbonate (SBC) to suppress postharvest anthracnose disease of papaya. SBC at various concentrations, 0, 1, 1.5, 2, 2.5 and 3% (w/v) was used as treatment against mycelial growth and spore germination of Colletotrichum gloeosporioides. After seven days of incubation, mycelial growth was completely inhibited by 3% SBC, which was statistically similar with 2 and 2.5% SBC (99.5% and 96.5% inhibition, respectively). Similar trend was observed with spores germination, where no spores were germinated after 8 h in 3% SBC solution, which was statistically identical with 2 and 2.5% SBC solution. In in vivo test, 2% SBC significantly reduced the disease incidence and severity where anthracnose disease was reduced up to 60% compared to the control. Therefore, 2% SBC can be expected to provide more effective control of anthracnose in papaya during storage.